2018
DOI: 10.1111/nyas.13634
|View full text |Cite
|
Sign up to set email alerts
|

Are there multiple ways to direct attention in working memory?

Abstract: In visual working memory tasks, memory for an item is enhanced if participants are told that the item is relatively more valuable than others presented within the same trial. Experiment 1 explored whether these probe value boosts (termed prioritization effects in previous literature) are affected by probe frequency (i.e., how often the more valuable item is tested). Participants were presented with four colored shapes sequentially and asked to recall the color of one probed item following a delay. They were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
112
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(142 citation statements)
references
References 43 publications
27
112
3
Order By: Relevance
“…It also differs from our procedure in that the retro-cue typically provides information about the probabilities that different items will be tested whereas all items had an equal probability of being tested in our studies. Indeed, Atkinson et al (2018) suggested that this may be an important methodological distinction, and that information regarding an item's value and its probability of being tested may motivate distinct forms of attentional direction.…”
Section: Discussionmentioning
confidence: 99%
“…It also differs from our procedure in that the retro-cue typically provides information about the probabilities that different items will be tested whereas all items had an equal probability of being tested in our studies. Indeed, Atkinson et al (2018) suggested that this may be an important methodological distinction, and that information regarding an item's value and its probability of being tested may motivate distinct forms of attentional direction.…”
Section: Discussionmentioning
confidence: 99%
“…Such an ability has already been reported in the context of prelearning manipulations, in which certain stimuli are preassociated before the memory experiment with different monetary values (Gong & Li, 2014;Infanti, Hickey, Menghi, & Turatto, 2017;Thomas, FitzGibbon, & Raymond, 2016;Wallis, Stokes, Arnold, & Nobre, 2015). It has recently been extended to more online processing and explored experimentally in a series of studies in which participants were instructed to remember a sequence of visual stimuli, but to prioritize certain items from within this sequence based on associated reward values (Atkinson et al, 2018;Hitch, Hu, Allen, & Baddeley, 2018;Hu, Allen, Baddeley, & Hitch, 2016;Hu, Hitch, Baddeley, Zhang, & Allen, 2014). This work consistently produces improved recall accuracy for prioritized items, alongside costs to deprioritized items, indicating that limited resources can be flexibly managed online to optimize task performance.…”
mentioning
confidence: 94%
“…While conceptually similar, the direction of attention via either reward values or visual cues is likely to involve at least some nonoverlapping forms of processing. We have so far assumed that reward-based manipulations (Atkinson et al, 2018;Hitch et al, 2018;Hu et al, 2016;Hu et al, 2014) primarily reflect endogenous control of directed attention; certain items are associated with higher reward values based on their serial position, and participants are encouraged to strategically utilize this points scheme when determining how to allocate their attention across the target items throughout each phase of the trial. Reliable effects of this manipulation are consistently observed even though the reward allocation is not predictive of which item will be tested.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These include, for example, the hypothesized phonological loop, which maintains verbal information, and the visuospatial sketchpad, which stores visual and spatial material (Baddeley, 2012). Although this established model concerning WM has been widely accepted, it has been recognized that the CES construct is the most complex system of WM ( Baddeley, 2012) with the need for clarity concerning its specific functions ( Atkinson et al , 2018;Baddeley, 1996).…”
Section: Introductionmentioning
confidence: 99%